Kepemimpinan dan Kepuasan Kerja: Mediasi Komunikasi - I Nengah Aristana; Ni Made Ernila Junipisa; Made Christin Dwitrayani (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
This study aims to see and analysis the influence of leadership on and job satisfaction, as well as to measure the role of communication as a mediating variable for the influence of leadership on job satisfaction in a villa business in Bali. The population of this research is all employees who work in the villa business in Bali. This study collected data using a questionnaire with accidental sampling method involving 109 employees at a villa business in Bali as respondents. To determine the effect of the independent variable on the dependent variable and the role of the mediating variable, this study analyzed the data using a path analysis approach with the Statistical Package for the Social Sciences (SPSS) 21 program. Meanwhile, to measure the role of the mediating variable using the variance accounted for (VAF) method. The results of this study indicate that leadership has a positive and significant effect on communication and job satisfaction, communication has a positive and significant effect on job satisfaction and communication is proven to be a partial mediator of the influence of leadership on employee job satisfaction in the villa business in Bali